Knowledge and Attitudes of Indigenous Papuan Communities Toward HIV/AIDS in Nabire District - Ema Rachmawati; Yunita Dyah Kusumaningrum; Afifah Machlaurin; Adelia Firandi; Putri Elsa Damayanti (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Human Immunodeficiency Virus (HIV) is a virus that attacks white blood cells and gradually weakens the immune system. Without appropriate treatment, HIV infection can progress to Acquired Immunodeficiency Syndrome (AIDS), a late stage marked by severe immune impairment. Papua is one of the provinces with the highest HIV/AIDS prevalence in Indonesia which indicating the importance of understanding community knowledge and attitudes as key elements in prevention and control efforts. This study aimed to describe the level of knowledge and attitudes toward HIV/AIDS among Indigenous Papuan communities in Nabire District. This study employed a descriptive cross-sectional design. Data were collected using a questionnaire that had been tested for validity and reliability, consisting of 23 knowledge items and 11 attitude items. A total of 300 respondents who met the inclusion criteria were included in the analysis. The findings showed that respondents’ knowledge was categorized as high (28%), moderate (32%), and low (39.67%). With regard to attitudes toward HIV/AIDS, 13% of respondents demonstrated good attitudes, 42.67% had moderate attitudes, and 43.67% showed poor attitudes. It can be concluded that the average level of knowledge among indigenous Papuan communities remains low, accompanied by less favorable attitudes toward HIV/AIDS. These findings indicate the need to strengthen more intensive, targeted, and socio-culturally appropriate educational programs to improve knowledge and promote more positive attitudes toward HIV/AIDS particularly in Nabire District.